Análise de desempenho baseada em simulação de redes WirelessHART - Nobre, Marcelo Henrique Ramalho (2012)
This dissertation describes the implementation of a WirelessHART networks simulation module for the Network Simulator 3, aiming for the acceptance of both on the present context of networks research and industry. For validating the module were imeplemented tests for attenuation, packet error rate, information transfer success rate and battery duration per station